Comparative study on the performance of a tubular solid oxide fuel cell fuelled by ammonia and hydrogen - Hajimolana, S.A.; Hussain, Mohd Azlan; Daud, Wan Mohd Ashri Wan (2011)
In this work, a dynamic model of a cathode-supported ammonia fed-tubular solid oxide fuel cell (NH3-SOFC) is developed and presented. The model accounts for processes such as diffusion, inherent impedance, transport (heat and mass transfer), electrochemical phenomena, activation and concentration polarizations for anode and cathode, as well as ammonia decomposition. The performance of NH3-SOFC is compared to that of H2-SOFC, it is found that with the same inlet values for both SOFCs under similar conditions, the performance of the cathode-supported NH3-SOFC is much higher than that for the H2-SOFC.